Base-scale entropy and energy analysis of flow characteristics of the two-phase flow. Issue 3 (21st September 2018) - Fan, Chunling; Fan, Qihua; Li, Haojie
ABSTRACT: In this paper, the base-scale entropy and root mean square energy analysis method are combined to present a simple and quick strategy to extract the features of the gas–liquid two-phase flow and to characterize the different flow patterns. In order to verify the effectiveness of the extracted features, we calculate their separability measure values. The experimental results show that the combined strategy proposed in this paper can not only distinguish the different flow patterns but also complement each other.